GRADING POLA PADA KASUS OVER SIZED ATASAN SEPATU DERBY BROGUE DI CV M JOINT EXCLUSIVE LEATHER CRAFT YOGYAKARTA - Siti Qomariyah; Anwar Hidayat (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2019)
The initial step of the shoe-making process begins with the design and pattern making. The main process in making patterns is also required grading sizes. Problems found in CV M Joint Exclusive Leather Craft is on the upper there was an oversize so that the decrease and increase in the upper is not balanced. The purpose of this final paper is to find out and solve the oversize problem in the upper. The method used was the experiment making grading patterns using CorelDRAW software. The results of the identification indicated that there were problems caused by technical errors used when grading shoe patterns. The efforts to prevent oversize of the unbalanced upper Brogue Derby shoes were by using the radialSharp triangle method, which was applied by using CorelDRAW software. The radial triangle method has been tested by making shoe samples, and this method can reduce the occurrence of over size in the upper